Pemberdayaan UMKM melalui Pengelolaan SDM, Pemasaran Digital, dan Pengelolaan Keuangan - Novi Fitria Hermiati; , Suriyanti Suriyanti; , Muhammad Kosim; , Nadia Meirani; Adinda Zalfaa Tri Alyaa (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This Community Service activity was carried out to increase the management capacity of Micro, Small, and Medium Enterprises (MSMEs) Warcaf Titik Singgah (WTS) engaged in the culinary sector. The main problems faced by partners include the lack of optimal human resource management, digital marketing, and financial recording. The absence of Standard Operating Procedures (SOPs) and clear job descriptions cause overlapping tasks between employees, while the use of social media as a means of digital marketing is still limited. On the other hand, simple financial recording has not been able to produce financial statements and calculate the Cost of Production (COG) accurately. Management capacity strengthening programs are carried out through socialization, training, demonstrations, technology implementation, mentoring, and evaluation in a participatory manner. Interventions include the preparation of SOPs and job descriptions, social media-based digital marketing training, the implementation of the Point of Sales (POS) system, and assistance in the preparation of digital financial statements. The results of the activities showed a significant increase in the understanding and skills of partners, characterized by the implementation of more structured SOPs, the use of social media to expand market reach, and the integration of POS systems in transaction recording, profit and loss reports, and HPP calculations. This program has a positive impact on operational efficiency, work professionalism, business management quality, and the competitiveness of MSMEs in the digital era.